Biliary complications of the hepatic echinococcosis of the child - Maquieira, Gonzalo (Cirugía del Uruguay, 1975)
One hundred and twenty cases of h2patic echinoccocosis in the child are reviewed. Biliary complications of these cases, which are 12. 5 % of them, are pointecl out. Surgical proceclures are reviewed. The removal of 1he parasyte, with the resection of the emergent aclventitia and closure of the, remaining cavity without any drainage is the procedure usually followed.